(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
The article describes the advantages and disadvantages of ASX-1 laboratory equipment and HVI 900 modern equipment, their differences, the selection and analysis of the most suitable equipment for a cotton ginning enterprise